A new voyage to Carolina - Lawson, John, 1674-1711 (University of North Carolina Press, 1967)
John Lawson's amazingly detailed yet lively book is easily one of the most valuable of the early histories of the Carolinas, and it is certainly one of the best travel accounts of the early 18th-century colonies. An inclusive account of the manners and customs of the Indian tribes of that day, it is also a minute report of the soil, climate, trees, plants, animals and fish in the Carolinas. Lawson's observation is keen and thorough; his style direct and vivid. He misses nothing and recounts all from the storms at sea to his impressions of New York in 1700, the trip down the coast to Charleston and his travels from there into North Carolina with his Indian guides. The first edition of this work was published in London in 1709. While various editions followed in the 18th century, including two in German, this edition is a true copy of the original and is the first to include a comprehensive index. It also contains "The Second Charter," "An Abstract of the Constitution of Carolina," Lawson's will and several previously unpublished letters written by Lawson. A number of DeBry woodcuts of John White's drawings of Indian life, sketches of the beasts of Carolina which appeared in the original 1709 edition and Lawson's map contribute additional interest to this volume